Perfluoroalkyl Substance Contamination Levels of Pike (Esox lucius L.) and Roach (Rutilus rutilus L.) from Selected Masurian Lakes in Eastern Europe. (3rd November 2021) - Surma, Magdalena; Hliwa, Piotr; Sznajder‐Katarzyńska, Katarzyna; Wiczkowski, Wiesław; Topolska, Joanna; Zieliński, Henryk
Abstract: Perfluoroalkyl and polyfluoroalkyl substances (PFAS) are of increased concern because of their bioaccumulation in humans and the biota, the health risk they pose to humans and other animals, and their persistence in the environment. In the present study, the occurrence of PFAS in selected tissues from pike ( Esox lucius L.) and roach ( Rutilus rutilus L.) collected from two lakes in the Masurian Lake District (Poland) in eastern Europe was addressed. Ten PFAS were analyzed in the tissue of the brain, liver, kidneys, gonads, and muscles by micro‐high‐performance liquid chromatography coupled with tandem mass spectrometry. Only perfluorooctane sulfonate (PFOS), perfluorooctanoic acid (PFOA), perfluorononanoic acid, and perfluorodecanoic acid were detected above the limit of quantification. Concentrations in pike and roach from Ełckie Lake and Hańcza Lake were estimated to be 14/27 and 4.4/3.2 ng/g wet weight, respectively. The contributions of PFOS and PFOA to the sum of PFAS calculated for particular tissues for each fish species were higher than those of the other analyzed compounds: PFOS was found to be predominant in fish from Ełckie Lake, whereas PFOA predominated in fish from Hańcza Lake. It was noted that PFAS concentrations in tissues declined in the following order: kidney > gonads ≈ brain > liver > muscle. The sum of the greatest estimated PFAS concentration was 9.7 ng/g wet weight in kidneys of pike collected from Hańcza Lake. No correlation was noted between PFAS concentration and fish size. The information provided in our study gives a better understanding of the potential dependencies in PFAS distribution and accumulation in biota. Environ Toxicol Chem 2021;40:3317–3327. © 2021 SETAC Abstract : The occurrence of selected perfluoroalkyl and polyfluoroalkyl substances (PFAS) in five tissues from pike ( Esox lucius L.) and roach ( Rutilus rutilus L.) collected from two lakes in eastern Europe (Poland) was tested by liquid chromatography‐tandem mass spectrometry. Different PFAS profiles in fish tissues were identified. Abbreviations: micro‐HPLC‐MS/MS = micro‐high‐performance liquid chromatography coupled with tandem mass spectrometry; PFOA = perfluorooctanoic acid; PFDA = perfluorodecanoic acid; PFNA = perfluorononanoic acid; PFOS = perfluorooctane sulfonate.